PENDAMPINGAN PETERNAK KAMBING PADA WILAYAH PENYANGGA PERUSAHAAN PTPV VII KABUPATEN LAMPUNG TENGAH - Muslimin, Muslimin; Hasnawati , Sri; Andriani , Lis; Dalimunthe, Nindytia Puspitasari (Faculty of Economics and Business Lampung University, 2024)
In the context of rural economic development, it is important to implement a social innovation collaborative model with social agents (industry, government, NGOs, and other organizations), where farmers take collective action to build a sustainable agricultural production system. Using the INRM (Integrated Natural Resource Management) method, the FEB Unila Community Service Team developed an Inclusive Social Business Model that encourages local farmer groups to collaborate on economic and social development activities through goat farming. INRM is a method of development-oriented research that aims to simultaneously reduce poverty, increase food security, and achieve environmental protection. The result of the community service is the formation of a livestock farmer group organization which is expected to become a local institution that plays the role of the Inclusive Social Business Model, encouraging sustainable economic and social programs to increase the income of farmers particularly, and the community of Mekar Jaya Village in general.